High-yield α-humulene production in Yarrowia lipolytica from waste cooking oil based on transcriptome analysis and metabolic engineering - Qi Guo; Qian-Qian Peng; Ying-Ying Chen; Ping Song; Xiao-Jun Ji; He Huang; Tian-Qiong Shi (Microbial Cell Factories, 2022)
Abstract Background α-Humulene is an important biologically active sesquiterpene, whose heterologous production in microorganisms is a promising alternative biotechnological process to plant extraction and chemical synthesis. In addition, the reduction of production expenses is also an extremely critical factor in the sustainable and industrial production of α-humulene. In order to meet the requirements of industrialization, finding renewable substitute feedstocks such as low cost or waste substrates for terpenoids production remains an area of active research. Results In this study, we investigated the feasibility of peroxisome-engineering strain to utilize waste cooking oil (WCO) for high production of α-humulene while reducing the cost. Subsequently, transcriptome analysis revealed differences in gene expression levels with different carbon sources. The results showed that single or combination regulations of target genes identified by transcriptome were effective to enhance the α-humulene titer. Finally, the engineered strain could produce 5.9 g/L α‐humulene in a 5‐L bioreactor. Conclusion To the best of our knowledge, this is the first report that converted WCO to α-humulene in peroxisome-engineering strain. These findings provide valuable insights into the high-level production of α-humulene in Y. lipolytica and its utilization in WCO bioconversion. Graphical Abstract